Parâmetros fitotécnicos e industriais de genótipos de sorgo sacarino na região central do Rio Grande do Sul - Bandeira, Andrieli Hedlund (2014)
The sweet sorghum stands out as a viable option for ethanol production during the harvest period between the cane sugar, thus allowing the extension of the period of production of alcohol and greater use of hand labor and rural other means of production. Therefore, the aim of research was to study the growth, development and technological parameters of sweet sorghum in two growing seasons. Two experiments were conducted in Santa Maria, located in the Central Depression of Rio Grande do Sul. The first experiment was conducted from October 2011 to April 2012, and the second trial from October 2012 to May 2013. In both experiments the experimental design was a randomized block with four replications. The sowing of sorghum was held in October , November and December each year , with a density of 120 000 plants per hectare after starting the emergency were performed assessments of growth and development , which occurred at an average interval of 15 days in the early maturation of sweet sorghum assessments of technological parameters were performed . The evaluation of the genotypes associated with sowing times is indicative of behavior in terms of the RS Central Depression, more precisely in the municipality of Santa Maria and helped to identify genotypes better adapted to local conditions.